Assessment of mental capacity and decision-making. (July 2018) - Barry, Caroline; Docherty, Mary
Abstract: Impaired capacity is very common in hospital inpatients, and assessment of capacity and decision-making should be a core skill for all clinicians. The Mental Capacity Act 2005 provides a clear framework for decision-making; it involves five key principles: the presumption of capacity; the obligation to maximize decision-making capacity; respect for an unwise decision if made by a competent adult; a duty to act in the best interests of an incapacitated person; and action in a manner that is least restrictive to them. Assessment of capacity in patients who are physically unwell can be challenging, and may need to be performed over multiple assessments. Efforts should be made to ensure that the patient's views are heard and respected, even if they lack capacity to consent to the treatment in question. Complexities arise when other legal frameworks such as the Mental Health Act 1983 need to be considered, and specialist legal or psychiatric opinion may be required in certain scenarios.